2020
DOI: 10.15252/emmm.201809271
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Notch signaling controls insulin transport in muscle

Abstract: The role of the endothelium is not just limited to acting as an inert barrier for facilitating blood transport. Endothelial cells (ECs), through expression of a repertoire of angiocrine molecules, regulate metabolic demands in an organ‐specific manner. Insulin flux across the endothelium to muscle cells is a rate‐limiting process influencing insulin‐mediated lowering of blood glucose. Here, we demonstrate that Notch signaling in ECs regulates insulin transport to muscle. Notch signaling activity was higher in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Mediated by nitric oxide, insulin increases the protein expression and secretion of VEGF ( Doronzo et al, 2004 ). Hasan et al (2020) demonstrated that obesity leads to higher activation of Notch signaling in ECs. This results in decreased insulin sensitivity and lower glucose uptake in the muscles.…”
Section: Metabolic Disorders Related To Obesity and Cardiovascular Comentioning
confidence: 99%
“…Mediated by nitric oxide, insulin increases the protein expression and secretion of VEGF ( Doronzo et al, 2004 ). Hasan et al (2020) demonstrated that obesity leads to higher activation of Notch signaling in ECs. This results in decreased insulin sensitivity and lower glucose uptake in the muscles.…”
Section: Metabolic Disorders Related To Obesity and Cardiovascular Comentioning
confidence: 99%
“…A recent study showed that Notch signaling in EC was involved in regulating insulin transport across the endothelium to muscle cells. Inhibition of Notch signaling affected caveolae formation in EC and improved insulin sensitivity, glucose tolerance, and glucose uptake in muscle in a high-fat diet model [ 25 ]. In contrast to EC, internalized insulin is degraded in VSMC, and directional transport of intact insulin is not observed.…”
Section: Structure and Signaling Of Insulin Receptors In Ec And Vsmcmentioning
confidence: 99%
“…A number of transport mechanisms have been proposed and are disrupted in the obese insulin-resistant state, including fluid-phase, clathrin vesicle and caveolae-mediated transport (83-86) (Figure 2). The molecular mechanisms are discussed in greater detail elsewhere (8,9), however, a role for endothelial Notch signalling in regulating caveolae-mediated transcytosis of insulin has recently been described (83). Sustained Notch signalling was associated with reduced insulin transcytosis as a consequence of reduced caveolae-related gene expression.…”
Section: Trans-endothelial Transport Of Glucosementioning
confidence: 99%
“…Sustained Notch signalling was associated with reduced insulin transcytosis as a consequence of reduced caveolae-related gene expression. Importantly, mice with HFD-induced insulin resistance displayed elevated endothelial Notch activity, that when inhibited, led to a restoration in caveolae-mediated insulin transport and improved glucose tolerance (83).…”
Section: Trans-endothelial Transport Of Glucosementioning
confidence: 99%